Kebermanfaatan: Sebuah Gambaran Work Engagement Pada Hakim - Vidya Nindhita; Avin Fadilla Helmi (Personifikasi: Jurnal Ilmu Psikologi, 2023)
The demands and heavy workload in a profession, especially related to the legal field, cause the importance of studying work engagement in their work. Work engagement is a condition of individuals who have positive thoughts and have high motivation in relation to their work. This is certainly influenced by the burdens and demands inherent in the work undertaken. This research reveals how the dynamics of work engagement exist in judges? What aspects and factors influence work engagement in judges? The research was conducted using a qualitative approach with a phenomenological method. The informants in this study were ten district court judges. The results showed that in addition to passion, dedication, and depth of focus, there is also usefulness as a dimension of the work engagement of judges. Factors that can affect work engagement are safety factors, working life factors, organizational, psychological, and emotional factors. Work engagement is formed by aspects and influenced by factors so that judges feel attached when at work, get new knowledge, reconcile (mediation), represent the justice system, and make the right decision to make prisoners aware.